Second medical use patents and compensation for the delay in marketing authorisations: the curious case of Vietnam - Le, V (Oxford University Press, 2022)
There has been a concern that developing countries which join new-generation FTAs might jeopardise their population’s access to medicines because those FTAs mandate TRIPS-plus patent standards. This article, however, argues that Vietnam, through its unusual legislative steps, has avoided increasing patent protection for medicines without (yet) violating international obligations. Its practice is examined via two specific patent-related issues: second medical uses and compensation for the delay in marketing authorisations. Regarding the first issue, the author finds that the law is deliberately ambiguous, as it neither rejects nor allows second medical use inventions. Regarding the second issue, Vietnam’s newly amended law in 2022 has arguably adopted a unique form of compensation: it waives the patent maintenance fees instead of extending the patent term. The paper concludes that because of the country’s sluggish local industry as well as its legislators’ struggle to keep pace with increasingly changing IP standards in the new FTAs, language ambiguity and lip service have become Vietnam’s weapons of choice.